Sciatic nerve injury related to hip replacement surgery: imaging detection by MR neurography despite susceptibility artifacts - Wolf, Marcel; Bäumer, Philipp; Pedro, Maria Teresa; Dombert, Thomas; Staub, Frank; Heiland, Sabine; Bendszus, Martin; Pham, Mirko (PLOS ONE, 2014)
Sciatic nerve palsy related to hip replacement surgery (HRS) is among the most common causes of sciatic neuropathies. The sciatic nerve may be injured by various different periprocedural mechanisms. The precise localization and extension of the nerve lesion, the determination of nerve continuity, lesion severity, and fascicular lesion distribution are essential for assessing the potential of spontaneous recovery and thereby avoiding delayed or inappropriate therapy. Adequate therapy is in many cases limited to conservative management, but in certain cases early surgical exploration and release of the nerve is indicated. Nerve-conduction-studies and electromyography are essential in the diagnosis of nerve injuries. In postsurgical nerve injuries, additional diagnostic imaging is important as well, in particular to detect or rule out direct mechanical compromise. Especially in the presence of metallic implants, commonly applied diagnostic imaging tests generally fail to adequately visualize nervous tissue. MRI has been deemed problematic due to implant-related artifacts after HRS. In this study, we describe for the first time the spectrum of imaging findings of Magnetic Resonance neurography (MRN) employing pulse sequences relatively insensitive to susceptibility artifacts (susceptibility insensitive MRN, siMRN) in a series of 9 patients with HRS procedure related sciatic nerve palsy. We were able to determine the localization and fascicular distribution of the sciatic nerve lesion in all 9 patients, which clearly showed on imaging predominant involvement of the peroneal more than the tibial division of the sciatic nerve. In 2 patients siMRN revealed direct mechanical compromise of the nerve by surgical material, and in one of these cases indication for surgical release of the sciatic nerve was based on siMRN. Thus, in selected cases of HRS related neuropathies, especially when surgical exploration of the nerve is considered, siMRN, with its potential to largely overcome implant related artifacts, is a useful diagnostic addition to nerve-conduction-studies and electromyography.
Gesehen am 24.09.2020